Clarifying Work Values Through Seasonal Employment: An Instrumental Case Study of Summer Camp Employment. (February 2023) - Warner, Robert P.; Sibthorp, Jim; Povilaitis, Victoria; Taylor, Jennifer M.
Emerging adults need opportunities to clarify their work values. Although researchers have examined how transitions and work experiences influence emerging adults' work values and job choices, less is known about how seasonal employment shapes work values. Using the theory of work adjustment as a guide, we conducted semi-structured interviews with 20–27 year olds ( n = 76; m age = 22.03, SD = 1.82) to understand how their seasonal employment at summer camps influenced their work values. We found that seasonal camp employment aligned with and helped participants clarify their desire for dynamic work that makes a difference and that offers a supportive social environment with adequate work-life balance. Our findings suggest that seasonal employment affords emerging adults important opportunities to discover, reinforce, and prune work values in a temporary employment setting. We conclude by discussing implications for emerging adults' career development and offer suggestions for career counselors.